PRINSIP-PRINSIP EKONOMI ISLAM DALAM MANAJEMEN KEUANGAN SYARIAH - Latifah, Eny; Abdullah, Rudi (JIDE : Journal Of International Development Economics, 2023)
The practice of the sharia financial system has existed since the glory of Islam until now. To maintain its existence, it is necessary to apply Islamic economic principles in sharia finance. Research using qualitative research methods with the type of library research aims to determine variations in Islamic economic principles in sharia financial management in Indonesia. The research results that show the principles of Islamic economics applied in sharia financial management in Indonesia are Tauhid, Prohibition of Usury'; Risk Sharing; Money as Potential Capital; Prohibition of Speculative (Maysir); Prohibition of fraud (gharar) Contracts/Agreements; Business activities must comply with sharia. The sharia financial system must also have the principle of Antaraddin minkum/ Willing and Willing; There is no party who oppresses or is wronged; Business results appear with costs; Profit comes with risk.